Strategi Pengembangan Usahatani Kumbili Sebagai Komoditas Pangan Lokal Di Kabupaten Pandeglang : Strategi Pengembangan Usahatani Kumbili Sebagai Komoditas Pangan Lokal Di Kabupaten Pandeglang - Widiati, Siti; Septianingsih, Ines (Journal of Food System & Agribusiness, 2024)
The strategy for developing Kumbili farming as a Local Food Commodity in Pandeglang Regency consists of internal and external factors. The aim of the research is to analyze the strategy for developing kumbili farming as a local food commodity in Pandeglang district. The type of research is a survey, the respondents of the research are 30 kumbili farmers, the data analysis used is SWOT analysis. The IFE matrix shows that the biggest strength is the relatively high price compared to other commodities, each score is 0.67 with a weight of 0.17 rating 4. Internal factors of weakness are the lack of application of technology and business management and the absence of diversification of processed food products, each score is 0 .67 and a weight of 0.17 a rating of 4. The EFE matrix shows the highest opportunity is increased market demand with a weight of 0.25 rating 4, a score of 1.00, the biggest threat to inconsistent product quality, a weight of 0.25, a rating of 4 and a score of 1.00. The IE matrix shows IFE on the X axis of 3.52 and a total EFE weight score on the Y axis of 3.38, this shows the development of farming in Grow and Build conditions. Based on the SWOT analysis, strategies can be applied: the S-O (Strength-Opportunity) strategy optimizes natural conditions suitable for growing conditions, optimizes support from government agencies, maintains and improves product quality based on farmer experience. The W-O (Weakness-Opportunity) strategy allocates resources to adopt relevant technologies, increase farmer skills and knowledge, establish partnerships, focus on market segmentation including export potential, optimize business scale. The S-T (Strength-Threaths) strategy optimizes the use of supportive natural conditions based on farmer experience, takes advantage of market potential, maintains product quality and is consistent so that it is able to determine prices. The W-T (Weakness-Threaths) strategy simplifies operations, implements management, collaborates on product research and development, improves supply chain management systems, considers appropriate technology to improve product efficiency and consistency, expands market share. The development of kumbili farming provides benefits: increasing income, diversifying farming, opening up opportunities to improve the economy, creating jobs, facilitating the community to achieve food self-sufficiency reducing dependence on imported food and family expenses to buy household food.